Trans narratives on school experiences—This is how we feel - Etxebarria-Perez-de-Nanclares, Olatz; Vizcarra Morales, Maria Teresa; López-Vélez, Ana Luisa; Gamito Gómez, Rakel (Frontiers in Psychology, 2024)
Introduction: The school environment remains unsafe for many trans people, where they are victims of discrimination, aggression and bullying causing them socioemotional and physical harm. Intersectionality and minority stress are contributing factors in this already challenging education environment. In many cases, the voices of trans people are not heard or listened to atin the school;, therefore, the aim of this study is to listen to their school experiences in order to identify key areas for improvement. Method: This study implemented a narrative research approach where 6 in-depth interviews were completed with trans participants from the Basque Country (Europe) and the United States of America that focused on 5 dimensions: being a trans, the role of school, lack of teachers education and ' training, segregation by gender and socioemotional well-being. The transcriptions of these interviews were coded using the Nvivo software in categorical systems in a deductive and inductive way. Results: The results show that the clearly binary society has a negative impact on trans people. In addition, the educational environment is still hostile for most of them in which the lack of teacher training and gender identity content in the curriculum have a negative impact on trans people and their experiences atin the school. Discussion: The findings supports the idea that the socially ingrained binarism is detrimental to punishes all those who step outside of the norm. It can also be said that the earlier the transition is made, the better the effect (clinical as well as socioemotional) on it has in their personal lives. For this to occur it is necessary to have access to information from an early age.